L’équilibre hydro-minéral chez le sandre (Stizostedion lucioperca l.1758) transfère de l'eau douce en milieux mixo-mesohalins et inversement - Neacșu, Ion; Crăciun, Valeriu; Crăciun, Margareta; Trandafirescu, Iulian (Cercetări Marine - Recherches Marines, 2026)
The sudden transfer of the pike perch from freshwater to sea water (17 g‰) causes some deep and irreversible changes in their hydromineral equilibrium leading to the death of the animals. A hydration of cells, a substantial accumulation of sodium in cells and an important loss of potassium and calcium take place. The animals transferred gradually survive by establishing a new hydro-mineral equilibrium. When the fishes adapted to sea water are suddenly brought back to freshwater, the hydro-mineral equilibrium specific to freshwater is established again, after minor modifications in the repartition of water and ions.